A pilot study on using Suction-Assisted Laryngoscopy Airway Decontamination techniques to assist endotracheal intubation by GlideScope® in a manikin simulating massive hematemesis. Issue 5 (September 2021) - Ko, Shing; Wong, Oi Fung; Wong, Ching Hin Kevin; Ma, Hing Man; Lit, Chau Hung Albert
Background: The Suction-Assisted Laryngoscopy and Airway Decontamination techniques are newly designed emergency airway management skills to assist endotracheal intubation with the complementary use of suction catheters and video laryngoscopes in patients with severe vomiting or massive hematemesis. Objectives: To evaluate the performance of emergency department doctors in using the two Suction-Assisted Laryngoscopy and Airway Decontamination techniques (level 1 and level 2) to assist endotracheal intubation by GlideScope ® in an airway manikin simulating massive hematemesis, the Nasco airway decontamination simulator. Methods: A total of 30 emergency department doctors were recruited in a pilot study. Their performance of using two levels of Suction-Assisted Laryngoscopy and Airway Decontamination techniques (Suction-Assisted Laryngoscopy and Airway Decontamination 1 and Suction-Assisted Laryngoscopy and Airway Decontamination 2) with two different suction catheters, the DuCanto suction catheter and Yankauer suction catheter, were compared with the conventional suction technique. The failed endotracheal intubation rates, time for intubation and number of attempts, amount of aspirated fluid, and the subjective ease of different methods by the participants were compared. Results: Irrespective the choice of suction catheter, endotracheal intubation in the manikin by using Suction-Assisted Laryngoscopy and Airway Decontamination 1 had the lowest failure rate which is much better than conventional suction technique (p = 0.012), smaller amount of aspiration compared with the conventional suction technique (p = 0.027), and comparable intubation time with the conventional suction technique (p = 0.850). Most participants were able to intubate the manikin successfully in the first attempt by Suction-Assisted Laryngoscopy and Airway Decontamination 1 with the DuCanto suction catheter, and they were of the opinion that such combination was the most preferred in performing endotracheal intubation. Conclusion: Suction-Assisted Laryngoscopy and Airway Decontamination 1 has the best performance in this manikin study, and Suction-Assisted Laryngoscopy and Airway Decontamination 1 with the DuCanto suction catheter was the most favorable method for endotracheal intubation in this manikin study by the participants.